Bimodal recognition of affective states with the features inspired from human visual and auditory perception system. Issue 4 (18th May 2019) - Selvaraj, Arivazhagan; Russel, Newlin Shebiah
Abstract: In this article, attention‐based mechanism with the enhancement on biologically inspired network for emotion recognition is proposed. Existing bio‐inspired models use multiscale and multiorientation architecture to gain discriminative power and to extract meticulous visual features. Prevailing HMAX model represents S2 layers by randomly selected prototype patches from training samples that increase the computational complexity and degrade the discerning ability. As eyes and mouth regions are the most powerful and reliable cues in determining facial emotions, they serve as the prototype patches for S2 layer in HMAX model. Audio code 4 book is constructed from mel‐frequency cepstral coefficients, temporal and spectral features processed by principal component analysis. Audio and video data features are fused to train support vector machine classifier. The attained results on eNTERFACE, surrey audio‐visual expressed emotion and acted facial expressions in the wild database datasets ascertain the efficiency of the proposed architecture for emotion recognition.